Analysis of Cd and Cu Heavy Metal Content in Climbing perch (Anabas testudineus) Derived from Rawa Taliwang Lake, West Sumbawa Regency - Khairuddin Khairuddin; M. Yamin; Kusmiyati Kusmiyati (Jurnal Biologi Tropis, 2022)
Many species of fish in Rawa Taliwang Lake can be used as bioindicators. Climbing perch (Anabas testudineus) is a species of freshwater fish that is used as a bioindicator. The aims of this study were: Want to know the heavy metal content of Copper (Cu) and Cadmium (Cd) in Climbing perch from Rawa Taliwang Lake to enrich the Environmental Knowledge course material. A special benefit is to protect consumers who consume fish from heavy metal contaminants. The research was conducted in Rawa Taliwang Lake, which is an area that is submerged in water. Methods Data collection was carried out by determining 2 research stations, namely in the east and west of the lake. Next, fishing is done using gill nets. Fish samples were taken from 3 to 4 fish at each station. The fish species taken were Climbing perch (Anabas testudineus). Then each fish sample was put into a plastic bag and then stored in a sample box. The research sample was then analyzed in the West Nusa Tenggara Health, Testing and Calibration laboratory. The data analysis method was carried out by taking muscle tissue from Climbing perch and then analyzing the content of heavy metals in the form of Copper (Cu), and Cadmium (Cd) using an Atomic Absorption Spectrophotometer. Measurement of heavy metals in fish tissue was carried out by adding concentrated HNO3 and HClO4, heated at a temperature of 60-70ÃÂºC for 2-3 hours until the solution was clear. Ready samples were measured by AAS using an air-acetylene flame. The measurement results show the presence of heavy metals Copper (Cu) and Cadmium (Cd) in the fish tissue studied. The conclusion of this study is that the heavy metal content in Climbing perch ÃÂ (Anabas testudineus) originating from Rawa Taliwang Lake to enrich the Environmental knowledge course material is; Copper (Cu) ranged from 0.067 ppm to 0.126 ppm, and Cadmium (Cd) ranged from 0.011 ppm to 0.016 ppm.